Unity in diversity, but only if you are beautiful: online self-representations and platform choices in virtual social environments - Lin, Bernice Xiangting (2024)
Diversity is embraced in various contexts, including virtual social environments. Avatars constitute one means of representing oneself online. This research explores the extent of diversity of human-like avatars in virtual social environments. Drawing on the hyperpersonal model and categorization-elaboration model, we assess user choices regarding avatar self-representations and virtual social platforms and demonstrate how diversity could be hindered in virtual social environments. We developed an avatar customization website and conducted two online studies to explore our hypotheses. Our results demonstrate that diversity in terms of facial symmetry, eye wrinkles, and forehead wrinkles were reduced in avatar self-representations than in actual selves. Diversity in hair color and freckles could be expanded online. Pro-diversity beliefs and perceived attractiveness of the platform moderated the effect of perceived diversity on platform choices. Our studies highlight nuances in pro-diversity platform choices and diversity of online self-representations and bear important theoretical implications on existing conceptual frameworks.